Hicks on Perfect Substitutes - Wilson, Edwin B. (Quarterly Journal of Economics, 1944)
Journal Article Hicks on Perfect Substitutes Get access Edwin B. Wilson Edwin B. Wilson Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 59, Issue 1, November 1944, Pages 134–140, https://doi.org/10.2307/1883261 Published: 01 November 1944